Laser Hemorrhoidoplasty Using Reusable Bare Fiber Combined Mucopexy on Grade IV Internal Hemorrhoid: A Case Report - Fadli Robby Amsriza; Rizka Fakhriani (Universitas Wijaya Kusuma Surabaya, 2024)
Background: Hemorrhoids are the most common anorectal disease, affecting millions worldwide. Hemorrhoids are categorized as